The Reality of Village Fund Budget Changes during the Covid-19 Pandemic Period (Study of Batuputih Village, Kangayan District, Sumenep Regency) - Elisa Agustina; Aprilya Dwi Yandari (PT FORMOSA CENDEKIA GLOBAL, 2022)
In 2020 the Village Fund Budget underwent a change due to theemergence of the Covid-19 pandemic in Batuputih Village, Kangayan District, Sumenep Regency which was transferred to direct Village Fund Cash Assistance (BLT-DD) and for Covid-19 Volunteers. The purpose of the study was to examine and determine the reality of changes in the village fund budget during the covid19 pandemic in Batuputih Village, Kangayan District, Sumenep Regency. This study used a qualitative descriptive approach with data collection techniques of observation, interviews, and documentation and analyzed using techniques source triangulation, and technical triangulation. The budget for the Batuputih village fund, Kangayan District, Sumenep Regency was transferred to 19% of the Village Fund Direct Cash Assistance (BLT-DD) which was divided into two stages as well as the function of preventing COVID-19, which was budgeted at Rp.13,470,000 for Covid-19 Volunteers holding deliberation. the hamlet and also the musdes or the holding of village deliberations until the resulting planning stage is approved by the Community and Village Empowerment Service (DPMD) along with the nominal percentage distributed to the community is also in accordance with what is stipulated by government regulations, which is 100%